The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/md.0000000000013821
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain volume and its relationship to characteristics of carotid plaques in asymptomatic patients

Abstract: Carotid plaque is an aggregate marker of exposure to vascular risk factors, which are linked to structural brain changes. We investigated prestroke global and regional changes in brain volume in a carotid plaque population of cognitively healthy individuals and the association between carotid plaque characteristics and these changes.A total of 76 participants were divided into healthy control (HC, n = 28), vulnerable plaque (n = 27) and stable plaque groups (n = 21). All subjects underwent carotid ultrasound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(32 reference statements)
2
3
0
Order By: Relevance
“…Secondly, our methodological approach replicates that of Liem et al, 2017 in a new sample, validating stacked learning as a useful tool for predicting individual differences from MRI-based measures. Finally, our results confirm some of the findings in the neuroimaging literature, namely that individually, cortical thickness and brain volumes are associated with CA-IMT ( Cardenas et al, 2012 , Muller et al, 2011 , Tuo et al, 2018 ). However, these associations are weak in comparison to that of FRS and do not add to that model’s predictive power.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Secondly, our methodological approach replicates that of Liem et al, 2017 in a new sample, validating stacked learning as a useful tool for predicting individual differences from MRI-based measures. Finally, our results confirm some of the findings in the neuroimaging literature, namely that individually, cortical thickness and brain volumes are associated with CA-IMT ( Cardenas et al, 2012 , Muller et al, 2011 , Tuo et al, 2018 ). However, these associations are weak in comparison to that of FRS and do not add to that model’s predictive power.…”
Section: Discussionsupporting
confidence: 90%
“…Separately from functional neuroimaging studies, there is structural brain imaging evidence indicating that CA-IMT is inversely associated with total brain tissue volume, as well as cortical tissue volume more specifically ( Muller et al, 2011 , Tuo et al, 2018 ). In parallel, however, other lines of evidence suggest no association between CA-IMT and total brain tissue volume or gray matter tissue volumes ( Cermakova et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, our methodological approach replicates that of Liem et al, 2016 20 in a new sample, validating stacked learning as a useful tool for predicting individual differences from MRI-based measures. Finally, our results confirm some of the findings in the neuroimaging literature, namely that individually, cortical thickness and brain volumes are associated with CA-IMT [14][15][16] . However, these associations are weak in comparison to that of FRS and do not add to that model's predictive power.…”
Section: Discussionsupporting
confidence: 90%
“…Other findings indicate that CA-IMT associates with lower cerebral blood flow in gray matter and across the entire brain 13 . Separately from functional neuroimaging studies, there is structural brain imaging evidence indicating that CA-IMT is inversely associated with total brain tissue volume, as well as cortical tissue volume more specifically 14,15 . In parallel, however, other lines of evidence suggest no association between CA-IMT and total brain tissue volume or gray matter tissue volumes 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that up to 5% of asymptomatic women and 12% of asymptomatic men over 80 years of age have a moderate carotid plaque (stenotic diameter of 50–70%) [1] . Apart from the risk of ischemic stroke, that in this population is relatively low with a reported annual incidence between 0.35 and 1.30% [2] , the presence of increased common carotid intima-media thickness (CC-IMT) and carotid artery stenosis have been associated to cognitive decline [3] , and reduced brain volumes [4] .…”
Section: Introductionmentioning
confidence: 99%